2019
DOI: 10.1111/ijpo.12500
|View full text |Cite
|
Sign up to set email alerts
|

Towards a circulating marker of hepato‐visceral fat excess: S100A4 in adolescent girls with polycystic ovary syndrome — Evidence from randomized clinical trials

Abstract: Summary S100A4 is a marker of subcutaneous adipose tissue dysfunction. Polycystic ovary syndrome (PCOS) is often driven by hepato‐visceral adiposity. PCOS phenotypes are normalized more by reduction of central fat with spironolactone/pioglitazone/metformin (SPIOMET) than by oral contraceptive (OC) treatment. We studied whether circulating S100A4 concentrations are high in adolescents with PCOS and, if so, whether they normalize more with OC or SPIOMET. Assessments included circulating S100A4, endocrine markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In addition, we observed an inverse correlation between S100A4 circulating levels and hepatic Arginase 1 (ARG1) gene expression. This goes in line with previous studies in which we reported that S100A4 could be a potential circulating marker of hepato-visceral fat excess in adolescent girls with PCOS (13). Moreover, an association between the decrease of hepato-visceral fat after pharmacological treatment of PCOS and the reduction of S100A4 circulating levels was found.…”
Section: European Journal Ofsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, we observed an inverse correlation between S100A4 circulating levels and hepatic Arginase 1 (ARG1) gene expression. This goes in line with previous studies in which we reported that S100A4 could be a potential circulating marker of hepato-visceral fat excess in adolescent girls with PCOS (13). Moreover, an association between the decrease of hepato-visceral fat after pharmacological treatment of PCOS and the reduction of S100A4 circulating levels was found.…”
Section: European Journal Ofsupporting
confidence: 92%
“…S100A4 is upregulated in sWAT vs vWAT CD11b+ cells but not in T cells, and its protein levels are higher in SVF from patients with obesity compared to adipocyte fraction S100A4 has been reported to be elevated in sWAT and vWAT from patients with obesity compared to lean individuals (12,13). In this context, we aimed to check the role of resident CD11b+ cells and T cells in the regulation of S100A4 in sWAT vs vWAT in a cohort of patients with severe obesity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In addition, S100A4, a marker of subcutaneous adipose tissue dysfunction, might become a circulating marker of hepato-visceral fat excess in adolescents with PCOS. 17 Pubertal obesity was one of the adverse factors underlying the pathophysiology of PCOS in adolescents. First, considering the role of mitochondrial dysfunction and systemic inflammation played in the pathogenesis of PCOS in adult patients, it was investigated that manifestations of oxidative stress and systemic inflammation also performed in overweight adolescents with PCOS, but less obvious in PCOS adolescents with normal weight due to the homeostasis control system and adaptive compensative mechanism of antioxidant defense in adolescence.…”
Section: Pathogenesismentioning
confidence: 99%
“…In mice, S100A4 levels were reduced after high fat diet and S1004 deficient mice had reduced insulin signaling, increased obesity, and liver inflammation [21]. In girls with PCOS, S100A4 levels were elevated and correlated with hepato-visceral adiposity; S100A4 and hepato-visceral fat decreased further with a combination spironolactone/pioglitazone/metformin (SPIOMET) treatment than with oral contraceptives [22].…”
Section: Beyond Reproduction: Current Understanding Of Comorbiditimentioning
confidence: 99%